2002
DOI: 10.1080/j.1600-0412.2002.811207.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy revisited in Benin City, Nigeria: analysis of 152 cases

Abstract: Background. Ectopic pregnancy is still a major health problem among women of childbearing age in our community. The majority of the patients with ectopic pregnancy are nulliparous in their mid twenties, with previous induced abortion(s) and or pelvic inflammatory disease. It remains a major challenge to the reproductive performance of women worldwide. Objective. The study is an analysis of the clinical profile of patients presenting with ectopic pregnancy, to investigate the current status of the incidence, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Pradhan et al is reporting that 49% of patients with ectopic pregnancy were nulliparous. (7) The peak age group was between 25 years and 29 years and the mean age was 29.52 and this factor is also comparable with other published studies (7,8) This finding maybe a reflection of the increase in the age at marriage. A definite change was seen in the following risk factorsprevious ectopic pregnancy, history of treatment for infertility, conception by artificial reproductive techniques, increase in the age at marriage and more nulliparous women developing ectopic pregnancy.…”
Section: Mode Of Presentation Number Percentagesupporting
confidence: 90%
“…Pradhan et al is reporting that 49% of patients with ectopic pregnancy were nulliparous. (7) The peak age group was between 25 years and 29 years and the mean age was 29.52 and this factor is also comparable with other published studies (7,8) This finding maybe a reflection of the increase in the age at marriage. A definite change was seen in the following risk factorsprevious ectopic pregnancy, history of treatment for infertility, conception by artificial reproductive techniques, increase in the age at marriage and more nulliparous women developing ectopic pregnancy.…”
Section: Mode Of Presentation Number Percentagesupporting
confidence: 90%
“…This macroscopic evidence of earlier pelvic inflammation was seen in 55.6%, a high rate when compared to 13.5% recorded in Ibadan (Ilesanmi, 1992), but similar to 54.9% recorded in Ilorin (Abdul, 2000) and 55% recorded in Lagos (Ola, 1999). Some authors have expressed the view that salpingitis as a consequence of induced abortion is a major aetiological factor in the high incidence of EP in Nigeria (Gharoro and Igbafe 2002, Oronsaye, 1979, Abdul, 2000. In some western countries, the chance that an abortion will result in ectopic pregnancy is negligible (Howie, 1995).…”
Section: Discussionsupporting
confidence: 67%
“…In Asia, where incidence is often on total deliveries, hospital based rates of 0.6 to 1.3% have been reported (Arup et al, 2007, Tsai et al, 1995, Khaleeque et al, 2001. Hospital based studies in Africa have documented rates on total deliveries of 1.5% and 3.29% in Guinea (Thonneau et al, 2002) and Ghana (Obed, 2006) respectively; while in Nigeria, the reported rates range from 0.48% to 4.38% (Makinde and Ogunniyi, 1990, Aboyeji et al, 2002, Gharoro and Igbafe, 2002, Ilesanmi and Sobowale, 1992, Ola et al, 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of nitrate in drinking water as a risk for cancer is controversial, high levels of nitrate in drinking water have been associated with increased mortality [15], and incidences of some cancers and lesions [16]. Spontaneous abortion, ectopic pregnancy [17], malignant lymphomas [18,19], and soft tissues sarcomas [20] have been reported in the Niger Delta region of Nigeria.…”
Section: Discussionmentioning
confidence: 99%